2014
DOI: 10.1016/j.virol.2014.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Avian reovirus-triggered apoptosis enhances both virus spread and the processing of the viral nonstructural muNS protein

Abstract: Avian reovirus non-structural protein muNS is partially cleaved in infected chicken embryo fibroblast cells to produce a 55-kDa carboxyterminal protein, termed muNSC, and a 17-kDa aminoterminal polypeptide, designated muNSN. In this study we demonstrate that muNS processing is catalyzed by a caspase 3-like protease activated during the course of avian reovirus infection. The cleavage site was mapped by site directed mutagenesis between residues Asp-154 and Ala-155 of the muNS sequence. Although muNS and muNSC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…Recently, two independent studies on ARV-induced apoptosis have concluded that ARV-induced apoptosis is favorable for virus spread and increasing the viral yield [19,31]. Our data seem contrary to those presented in those two papers, but in fact, their results and ours may actually be compatible.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, two independent studies on ARV-induced apoptosis have concluded that ARV-induced apoptosis is favorable for virus spread and increasing the viral yield [19,31]. Our data seem contrary to those presented in those two papers, but in fact, their results and ours may actually be compatible.…”
Section: Discussioncontrasting
confidence: 99%
“…In spite of the presence of TLR4 ligand (LPS), EcN colonization resulted in a more substantial decrease of apoptotic and TLR4 expressing MNCs than LGG, emphasizing the complexity of the TLR signaling pathways. Virus‐triggered apoptosis is a conserved innate immune defense strategy of eliminating virus infected cells; however, it may also aid the pathogen by facilitating its spread . Therefore, the EcN and LGG‐mediated counteraction of the HRV‐induced apoptosis that we observed in this study could have limited the HRV replication.…”
Section: Discussionmentioning
confidence: 75%
“…The M 115 residue was determined to be the best candidate as M 94 is not conserved among all PRV isolates, and M 85 and M 169 are unlikely due to the sizes of the proteins generated. Post-translational cleavage to generate µNSC as shown for ARV µNS cannot be excluded, although the specific proteolytic cleavage site in the ARV protein is not conserved in PRV [2,33,53]. The different µNS size variants, i.e., full-length µNS and the 70 kDa variant with putative translation initiation at M 115 , may differ in their interactions with other PRV proteins.…”
Section: Discussionmentioning
confidence: 99%